Do exogenous application of thiamine mitigates low soil base saturation effects on bell pepper plants? - Vendruscolo, Eduardo Pradi; Alves, Vitória Dantas; Sant'Ana, Gabriela Rodrigues; de Almeida Prado Bortolheiro, Fernanda Pacheco [UNESP]; Martins, Murilo Battistuzzi; de Castro Seron, Cássio; de Souza, Maria Ingrid; Dantas, Thaise (Revista de Agricultura Neotropical, 2022)
The intensive use of land to produce vegetables results in high soil degradation and cultivated area. The use of techniques and resources that make production possible under unfavorable conditions can be decisive for agriculture. Thus, this study aimed to evaluate the isolated and joint effects of liming and thiamine application on the development of bell pepper plants. The treatments consisted of three different soil base saturation (36, 60, and 80%), combined with foliar application of thiamine (with and without) at a concentration of 100 mg L-1. It was found that thiamine mitigates the effects of low base saturation on the physiological traits of bell pepper plants. The increments related to the water use efficiency and instantaneous carboxylation efficiency allowed greater development of plants treated with thiamine. In addition, the application of thiamine is advantageous in cases where planting is carried out under conditions of low base saturation, followed by an adequate supply of nutrients or systems in which there is a partial or total correction of the soil chemical characteristics, promoting the development of plants and increased physiological activity.
Aplicação exógena de tiamina ameniza os efeitos da baixa saturação de bases do solo sobre plantas de pimentão?
Keywords: Biostimulants; Carbon fixation; Plant protection; Soil management